A study to assess the blood glucose level among diagnosed cases of tuberculosis registered at a tuberculosis unit of Bhopal city, Madhya Pradesh, India - Vivek Nagar; Devendra Gour; Vishwanath Arutagi; Lokendra Dave; Padma Bhatia; Ankur Joshi; DK Pal (Universiti Kebangsaan Malaysia, 2015)
Background: The incidence of diabetes mellitus (DM) is increasing worldwide, especially in developing countries where tuberculosis (TB) is most prevalent. Nearly one-third of world’s population is infected with Mycobacterium tuberculosis. Diabetes and TB may complicate each other at many levels. Systematic review of screening conducted in multiple settings showed that screening of patients with TB for DM also yielded high prevalence of diabetes ranging from 1.9% to 35%. Objective: This study aimed to assess the blood glucose level among diagnosed cases of TB registered at a District Tuberculosis Center in Bhopal. Materials and Methods: This study is a cross-sectional study carried out in a TB unit (District Tuberculosis Center), Bhopal, on all registered cases of TB above 18 years. All patients who gave their consent during the study period of October 2013 to March 2014 were included Results: Out of 260 subjects enrolled for this study, complete details and blood glucose values were available for 220 subjects. Of the 220 subjects, 34 (15.4%) were found to have DM and 25 (11.3%) had previous diagnosis of DM; 9 (4.09%) were newly diagnosed. The prevalence of DM among patients with TB was significantly higher among males aged 450 years and with pulmonary TB. Conclusion: Results of this study re-echo the need to raise awareness of screening for DM in persons with TB. Study finding shows the high prevalence of DM in patients with TB in Bhopal, and that a significant proportion of patients with DM may not be aware of their glucose status. Screening of patients with TB for DM is feasible, effective, and comprehensive approach that could lead to improved care and better patient outcomes.